2009
DOI: 10.17221/30/2008-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

The development of population structure of Cryphonectria parasitica on European chestnut (Castanea sativa Mill.) in the Experimental Castanetarium Horné Lefantovce, observed over a 12-year study period

Abstract: ABSTRACT:We studied occurrence of chestnut blight disease in the Experimental Castanetarium Horné Lefantovce, SW Slovakia. The study ran in years 2006-2007 on a set consisting of 889 chestnut trees growing in the clonal orchard on Biological Plot 105. From this number, 857 trees were found healthy without disease symptoms. The chestnut blight disease was identified on 32 of them. The infected trees were examined for presence of pycnidia and perithecia of the causal agent. In all positive cases, the observed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In these countries, the database is useful to trace the history and origin of introductions and movements among Table 3. They also provide information on the reproduction of C. parasitica in these areas, and to evaluate the possible success of biological control programmes using hypovirulence, which is highly dependent on the clonality of the pathogen population (Gurer et al 2001;Milgroom and Cortesi 1999;Milgroom et al 2008;Adamcikova et al 2009;Jankovsky et al 2010). 4 Normalized Shannon diversity index (Sheldon 1969). areas.…”
Section: Discussionmentioning
confidence: 99%
“…In these countries, the database is useful to trace the history and origin of introductions and movements among Table 3. They also provide information on the reproduction of C. parasitica in these areas, and to evaluate the possible success of biological control programmes using hypovirulence, which is highly dependent on the clonality of the pathogen population (Gurer et al 2001;Milgroom and Cortesi 1999;Milgroom et al 2008;Adamcikova et al 2009;Jankovsky et al 2010). 4 Normalized Shannon diversity index (Sheldon 1969). areas.…”
Section: Discussionmentioning
confidence: 99%
“…G ravatt (1952) reported that fruiting of C. parasitica was rare on Q. stellata ; even after 2 years after inoculation pycnidia were present within 13% of the inoculation wounds on Q. coccinea (N ash and S tambaugh 1987). In our study, no perithecia were detected on bark samples obtained from Quercus spp., but the teleomorph on C. sativa is known from Slovakia (A damčíková and J uhásová 2002; A damčíková et al. 2009).…”
Section: Discussionmentioning
confidence: 99%